The study on the mechanical characteristics of articular cartilage in simulated microgravity - Niu, Hai-Jun; Wang, Qing; Wang, Yue-Xiang; Li, Ang; Sun, Lian-Wen; Yan, Yan; Fan, Fan; Li, De-Yu; Fan, Yu-Bo (Acta mechanica Sinica, 2012)
The microgravity environment of a long-term space flight may induce acute changes in an astronaut＇s musculo-skeletal systems. This study explores the effects of simulated microgravity on the mechanical characteristics of articular cartilage. Six rats underwent tail suspension for 14 days and six additional rats were kept under normal earth gravity as controls. Swelling strains were measured using high-frequency ultrasound in all cartilage samples subject to osmotic loading. Site-specific swelling strain data were used in a triphasic theoretical model of cartilage swelling to determine the uniaxial modulus of the cartilage solid matrix. No severe surface irregularities were found in the cartilage samples obtained from the control or tail-suspended groups. For the tail-suspended group, the thickness of the cartilage at a specified site, as determined by ultrasound echo, showed a minor decrease. The uniaxial modulus of articular cartilage at the specified site decreased significantly, from （6.31 ± 3.37） MPa to （5.05 ± 2.98）MPa （p 〈 0.05）. The histology- stained image of a cartilage sample also showed a reduced number of chondrocytes and decreased degree of matrix staining. These results demonstrated that the 14 d simulated microgravity induced significant effects on the mechanical characteristics of articular cartilage. This study is the first attempt to explore the effects of simulated microgravity on the mechanical characteristics of articular cartilage using an osmotic loading method and a triphasic model. The conclusions may provide reference information for manned space flights and a better understanding of the effects of microgravity on the skeletal system.